Fortnite: The business model pattern behind the scene - Timo Schöber; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2020)
We analyse the business model pattern behind the success of the Fortnite game. A theoretical model is used to examine the conditions where a Freemium strategy is appropriate. We also shed light on the structure of the in-game-shop and we analyse several features from a marketing perspective.
Keywords: 330; Fortnite; business model pattern; gaming; e-Sports